Cultural Diversity: A Matter of Measurement - Peter Nijkamp; Jacques Poot (Institute for the Study of Labor (IZA), 2015)
Cultural diversity - in various forms - has in recent years turned into a prominent and relevant research and policy issue. There is an avalanche of studies across many disciplines that measure and analyse cultural diversity and its impacts. Based on different perspectives and features of the available data, a great variety of diversity indicators have emerged. The present paper aims to highlight some critical issues involved in applying such measures of cultural diversity. A selection of commonly used or recently advocated measures are reviewed. Measures of population diversity can be calculated at different spatial scales and used to analyse spatio-temporal heterogeneity. Additionally, there is a growing interest in measuring spatial dependence, particularly in the form of segregation or clusters. We conclude that there will be in the future considerable scope for adopting multidimensional and cultural distance-weighted measures of diversity. Such measures will be increasingly calculated by means of rich geo-referenced longitudinal micro data. However, adopted measures must be better motivated by behavioural theories. Further research on the determinants and impacts of observed measures of diversity is also likely to be fruitful, particularly in a dynamical setting.
Keywords: C00; D63; J15; R23; Z13; 330; diversity; dissimilarity measurement; ethnicity; culture; segregation; polarization; fractionalization